2009
DOI: 10.1016/j.polymer.2009.01.052
|View full text |Cite
|
Sign up to set email alerts
|

Network formation in nitroxide-mediated radical copolymerization of styrene and divinylbenzene in miniemulsion: Effect of macroinitiator hydrophilicity

Abstract: a b s t r a c tNitroxide-mediated crosslinking radical copolymerizations of styrene and divinylbenzene have been carried out in aqueous miniemulsion with Dowfax 8390 as surfactant at 125 C employing TEMPO-based macroinitiators of various hydrophilicities (random copolymers comprising styrene and methyl acrylate). The pendant conversion (i.e. the degree of crosslinking) increased with increasing macroinitiator hydrophilicity and with decreasing particle size. It is proposed that a concentration gradient is gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Dispersed NMP systems are very complex, and a number of intrinsic features may set these systems apart from their homogeneous counterparts in bulk and solution 3. In addition to the phenomena of compartmentalization and nitroxide partitioning, there may also be effects of the oil/water interface,40–44 enhanced (spontaneous) radical generation,45, 46 as well as possibly also effects of the Laplace pressure within particles/droplets 47. Moreover, particle size distributions are often relatively broad (especially in miniemulsion systems), which makes quantitative analysis of experimental data with regards to particle size effects difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Dispersed NMP systems are very complex, and a number of intrinsic features may set these systems apart from their homogeneous counterparts in bulk and solution 3. In addition to the phenomena of compartmentalization and nitroxide partitioning, there may also be effects of the oil/water interface,40–44 enhanced (spontaneous) radical generation,45, 46 as well as possibly also effects of the Laplace pressure within particles/droplets 47. Moreover, particle size distributions are often relatively broad (especially in miniemulsion systems), which makes quantitative analysis of experimental data with regards to particle size effects difficult.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies involved molecular or macromolecular inisurfs in controlled radical polymerization [38][39][40][41][42][43]. To the best of our knowledge, only one work reported the use of a molecular inisurf for controlled radical polymerization [38].…”
Section: )mentioning
confidence: 99%
“…A comprehensive literature survey found only a few reports on the heterogeneous CLRP with branching/crosslinking. Okubo's group studied crosslinking kinetics in NMP miniemulsion polymerization of styrene (St) with divinylbenzene (DVB) and made some interesting comparisons to the corresponding bulk/solution polymerization systems . It was found that DVB was consumed slower in miniemulsion polymerization than in bulk/solution polymerization .…”
Section: Introductionmentioning
confidence: 99%
“…The crosslinking density increased as the miniemulsion polymerization proceeded while the density decreased with monomer conversion in the bulk system . Furthermore, the oil–water interface was found to have a large effect on crosslinking reactions in the miniemulsion . Other researchers focused on synthesizing crosslinked particles such as core‐shell and hollow particles by CLRP in various heterogeneous systems .…”
Section: Introductionmentioning
confidence: 99%